Оцінювання закону розподілу величини збитків унаслідок реалізації загрози “Відсутність або недостатність технічного обслуговування” - Мохор, В.В.; Цуркан, В.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
The problem of estimation of size distribution law of damages in the absence or insufficient sample size of the universe and the initial data suggested approach to finding the most expected value of losses due to information security threats.